2013
DOI: 10.1039/c2cp43727a
|View full text |Cite
|
Sign up to set email alerts
|

Possible presence of hydrophilic SO3H nanoclusters on the surface of dry ultrathin Nafion® films: a positron annihilation study

Abstract: Solutions of Nafion® with an ion exchange capacity (IEC) of 0.91 meq g(-1), which are on the verge of the formation of SO(3)H nanoclusters, were spin coated on silicon (Si), glassy carbon (GC) and platinum/silicon (Pt/Si) substrates to form films of up to 256 nm thickness. Nanostructure of the films was studied using Doppler broadening of annihilation radiation (DBAR), positron annihilation lifetime (PAL), X-ray photoelectron spectroscopy (XPS), an atomic force microscope (AFM) and contact angle measurements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 58 publications
(66 reference statements)
2
70
0
Order By: Relevance
“…From Figure , the strong thickness dependency of CTE for thinner Nafion films (<60 nm) can be noted. Similar trends for thickness dependency of other Nafion thin films properties including proton conductivity and water uptake has also been reported where films below 60 nm show stronger changes in properties compared to thicker films . The increase in CTE with decreasing film thickness has been attributed to unfavorable interaction between the substrate and the polymer for PS on Si .…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…From Figure , the strong thickness dependency of CTE for thinner Nafion films (<60 nm) can be noted. Similar trends for thickness dependency of other Nafion thin films properties including proton conductivity and water uptake has also been reported where films below 60 nm show stronger changes in properties compared to thicker films . The increase in CTE with decreasing film thickness has been attributed to unfavorable interaction between the substrate and the polymer for PS on Si .…”
Section: Resultssupporting
confidence: 75%
“…Similar trends for thickness dependency of other Nafion thin films properties including proton conductivity and water uptake has also been reported where films below 60 nm show stronger changes in properties compared to thicker films. 4,27,[29][30][31][32][33][34][35][36][37][38] The increase in CTE with decreasing film thickness has been attributed to unfavorable interaction between the substrate and the polymer for PS on Si. 39 It has been argued that the unfavorable interactions with the substrates promote polymer chain mobility and thereby an increased expansivity compared to the bulk polymer.…”
Section: Thermal Expansion Coefficient Of Films On Siomentioning
confidence: 99%
“…The structural and transport properties of the commercial Nafion membranes of various equivalent weights and thickness have been studied extensively . For the thin films, the focus has been on the effect of annealing, thickness and on the substrate on which they are cast . To have realistic applications, the films should be mechanically robust and strongly acidic.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] For the thin films, the focus has been on the effect of annealing, [20][21][22] thickness [23][24][25] and on the substrateo nw hicht hey are cast. [22,[26][27][28] To have realistic applications, the films should be mechanically robust and strongly acidic.H owever,f reshly prepared films are reportedt ob eb rittle and soluble in polar solvents including warm water. [29] Gebel et al [20] have demonstrated that heating impartsc rystallinity to the films, with ac oncomitantd ecrease in solubility.Achange in the structure of the ionomer from micelle to reverse micelle also takes place upon heating.…”
Section: Introductionmentioning
confidence: 99%